2022
DOI: 10.3390/app12073476
|View full text |Cite
|
Sign up to set email alerts
|

Does Nanosilver Have a Pronounced Toxic Effect on Humans?

Abstract: Due to the development of high-tech industries, the modern world is characterized by the increased production and consumption of nanoparticles (NPs) and nanomaterials. Among produced metal nanoparticles, silver nanoparticles are widely used in everyday life products, cosmetics, and medicine. It has already been established that, in nanoscale form, many even inert materials become toxic. Therefore, the study of the toxicity of various substances in nanoscale form is an urgent scientific task. There is now a bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Nevertheless, in a recent review, Ivlieva and collaborators concluded that the toxicity is mostly due to the liberation of Ag + and not from the nanoparticle itself, showing the importance of a good stability of the AgNPs for its safety. 27 Additionally, Maziero and her team have shown that AgNPs stabilized with Gum Arabic Protein revealed adverse effects in zebrafish species but not in Sprague Dawley rats for 28 days in doses up to 10.0 mg/kg which shows the potential of their usage and the importance of their study. 28 Thus, the purpose of this study was to synthesize and characterize AgNPs functionalized with glucose (G-AgNPs) and further study their cytotoxic and cellular effect in PCa cells resistant to ADT.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, in a recent review, Ivlieva and collaborators concluded that the toxicity is mostly due to the liberation of Ag + and not from the nanoparticle itself, showing the importance of a good stability of the AgNPs for its safety. 27 Additionally, Maziero and her team have shown that AgNPs stabilized with Gum Arabic Protein revealed adverse effects in zebrafish species but not in Sprague Dawley rats for 28 days in doses up to 10.0 mg/kg which shows the potential of their usage and the importance of their study. 28 Thus, the purpose of this study was to synthesize and characterize AgNPs functionalized with glucose (G-AgNPs) and further study their cytotoxic and cellular effect in PCa cells resistant to ADT.…”
Section: Introductionmentioning
confidence: 99%